Diet Composition of the Wild Stump-Tailed Macaque(Macaca arctoides) in Perlis State Park, Peninsular Malaysia, Using a Chloroplast tRNL DNA Metabarcoding Approach: A Preliminary Study - Nur Azimah, Osman; Muhammad Abu Bakar, Abdul Latiff; Mohd Ridwan, Abd Rahman; Salmah, Yaakop; Shukor, Md Nor; Badrul Munir, Md Zain (MDPI, 2020)
Understanding dietary diversity is a fundamental task in the study of stump-tailed macaque, Macaca arctoides in its natural habitat. However, direct feeding observation and morphological identification using fecal samples are not effective and nearly impossible to obtain in natural habitats because this species is sensitive to human presence. As ecological methods are challenging and time-consuming, DNA metabarcoding offers a more powerful assessment of the diet. We used a chloroplast tRNL DNA metabarcoding approach to identify the diversity of plants consumed by free-ranging M. arctoides in the Malaysia–Thailand border region located in Perlis State Park, Peninsular Malaysia. DNA was extracted from three fecal samples, and chloroplast tRNL DNA was amplified and sequenced using the Illumina MiniSeq platform. Sequences were analyzed using the CLC Genomic Workbench software. A total of 145 plant species from 46 families were successfully identified as being consumed by M. arctoides. The most abundant species were yellow saraca, Saraca thaipingensis (11.70%), common fig, Ficus carica (9.33%), aramata, Clathrotropis brachypetala (5.90%), sea fig, Ficus superba (5.44%), and envireira, Malmea dielsiana (1.70%). However, Clathrotropis and Malmea are not considered Malaysian trees because of limited data available from Malaysian plant DNA. Our study is the first to identify plant taxa up to the species level consumed by stump-tailed macaques based on a DNA metabarcoding approach. This result provides an important understanding on diet of wild M. arctoides that only reside in Perlis State Park, Malaysia.